Role of Technological advancements in Effective Supply Chain Management: An Empirical Study (International Journal of Food and Nutritional Sciences, 2022)
Emerging advancement of technology in numerous sectors because of internet services, the sector of supply chain management has grabbed the most of the opportunities for the establishment of its hand in Indian economy. This movement of information technology is the key for supply chain management as majority of its activities are transferred to web-based technology. The movement of information between suppliers and company, company to consumer is essential for its success. Using technology in supply chain management is highly pre-condition for effective control in today’s highly competitive market. Advanced technology is helping in creating better visibility in supply chain management, reduction of operational costs and enhancement of satisfaction and retention of customers. Despite the importance of technology acknowledgement in supply chain management, it is not utilised fully. The companies are shifting towards digital supply chain with the assistance of swift changes in technology and application of information technology like “Electronic Data Exchange (EDI), Radio Frequency Identification (RFID), Bar Code, Electronic Commerce, Decision Support system, Enterprises Resource Planning (ERP) package, etc.” 211 respondents were considered in the study as a sample size. Mean and T-test was applied in the study to find the outcome.